THE TRACE-ELEMENTS CD AND SB OF THE MN-FE ORE FROM WESTERN EUPHRATES REGION THE KEBAN DISTRICT, PROVINCE ELAZIG EASTERN TURKEY - CELEBI, H; PEKER, I; UTLU, F (Gustav Fischer Verlag Jena, 1995)
In contents of present article are the Cd and Sb-concentrations of 20 Ag bearing oxydic Mn-Fe ore samples from the Keban district geochemically investigated and interpreted. The analysis yield that the investigated ore contains just an average of 31 ppm Cd and 28 ppm Sb. Their enrichment factors are in relation to the clarke values 150 and 140 times which have not any economic importance and environmental influences. The results have shown that there was not a significant interrelation between Cd, Sb, Zn and Pb distributions and Mn and Fe concentrations. That is due to undersaturation of Cd in sphalerite and Sb in galena. In the other hand, correlate the Cd, Zn, and Pb contents with the Cd/Sb, Zn/Cd, and Pb/Sb ratios in each case because of the preferred substitutions of Zn, Sb and Pb by Cd and Sb during crystallisation. The positive correlation between Mn and Fe concentrations refers to a common separation of these elements. The mean of Mn/Fe ratio is about 0.9 and corresponds to that of the submarine hydrothermal ore deposits that is supported by barite existence and low Cu, Zn, and Co concentrations.